Masculinities, vulnerability and negotiated identity: Understanding the reporting behaviours of men who experience violence or otherwise harmful behaviour, within a sex work context - JORDAN DAWSON (2022)
Context The focus of sex work related discussions most commonly falls on female providers of sexual services, and male purchasers. As a result, the often victim-oriented policy response in England and Wales falls short of truly addressing the needs of men who are involved in the sale of sex, with there being limited support available for them and a systemic approach which does not fully recognise the potential for men to face harm within this context. Methods The aim of this study is to explore experiences of and reactions to violence, and otherwise harmful behaviours, faced by men in the context of their sex working, by understanding the lived realities of a sample of men who engage in this type of work. The study takes a phased approach which combines an initial informative quantitative survey, with three subsequent phases of semi-structured interviews with male sex workers, sex work-focused practitioners and police officers. The method is guided by feminist research principles which suggest that reality is situated within those with lived experience, and also by an element of co-creation which has grounded this study within the perspectives of male sex workers from its conception. Findings The findings of this research suggest that all of the men involved in the study had faced at least one of the violent or otherwise harmful behaviours outlined, though reporting of these behaviours was not at all common. Discussions with the male sex working participants, practitioners and the police highlighted the issues related to the structural influences of authority, such as the police, and the social environment, and the internalisation of these wider factors, which create barriers to reporting for groups such as male sex workers and others who face similar social marginalisation. Conclusions This study challenges existing gendered understandings of violence and otherwise harmful behaviour within a sex work context, by highlighting the harmful experiences of men. By exploring these experiences and the reporting behaviours of those involved, the study also proposes a new framework for understanding barriers to reporting, which suggests that these are formed through the influences of formal and informal measures of social control, and the internalisation of these outside influences by the individual. By better understanding the experiences of men, and the barriers to their reporting, this study attempts to nuance a gendered discussion. Within, I propose that in order to better support male sex workers, responses must begin by appreciating the heterogeneity of those involved in sex work and the influence of their individual circumstances and the social environment on their willingness to seek support.